Killing giants : 10 strategies to topple the Goliath in your industry - Denny, Stephen, 1962- (New York : Portfolio/Penguin, 2011)
Counsels business leaders on how to take advantage of the inherent weaknesses of larger competitors, profiling more than thirty companies to demonstrate how smaller and more versatile organizations can implement profitable strategies.
Includes index.
Keywords: Marketing; Strategic planning; Business planning